VERBAL PHRASE IN THE SPANISH OF CARAL: SYNTACfiC INTERFERENCES - Galvez, Judith (2008)
This articlc describes some transformations in the verbal syntactic structures in the Spanishof Cara! , due to syntactic intcrferences coming from linguistic contacts generated longago in history. Quechua as a substrate language has triggered such changes in monolingualSpanish, especially because of the large numbers of Andean migrants comingto the zone.